Educational Attainment as a Predictor of HIV Testing Uptake Among Women of Child-Bearing Age: Analysis of 2014 Demographic and Health Survey in Zambia - Muyunda, Brian; Musonda, Patrick; Mee, Paul; Todd, Jim; Michelo, Charles (Frontiers in Public Health, 2018)
Abstract Background Globally, an estimated 150,000 children were newly infected with HIV in 2015, over 90% of them in Sub-Saharan Africa. In Zambia, approximately 500,000 babies are born to HIV positive mothers every year, and without intervention 40,000 of them would acquire the infection. Studies have shown a strong association between education and HIV prevalence, but in Zambia, this association has not been demonstrated. There is little published information on the association between educational attainment and HIV testing uptake among pregnant women, which is fundamental in understanding the mother to child transmission of HIV. This study investigated whether educational attainment is associated with uptake of HIV testing among women of reproductive age in Zambia. Methods Data were taken from Zambia Demographic and Health Survey in 2014 (ZDHS14). The analysis consisted of all women aged 15-49 years, who responded to a question about HIV testing from ZDHS. Multi-variable logistic regression was used to determine whether educational attainment is associated with uptake of HIV testing among women of reproductive age in Zambia. Results Educational attainment was strongly associated with HIV testing among 15,388 women of child bearing age [AOR 3.8, 95% CI 1.7-8.2; p=0.001]. HIV testing differed greatly by economic social standing of woman with an increased uptake among women with higher wealth index [AOR 4.4, 95% CI 1.9-9.9; p=0.001]. Additionally, HIV testing was observed to be higher among the older women 25-34 years compared to the young women 15-19 years [AOR 2.3, 95% CI 1.3-4.3; p=0.007]. Conclusions This study revealed educational attainment to be a strong predictor of HIV testing among women of child bearing age in this population. High HIV testing uptake among educated pregnant women indicated that low-educated women may not fully realize the benefits of testing for HIV. Therefore, strengthening HIV testing in rural health facilities and providing initiatives to overcome barriers to testing among women with no formal education may help reduce vertical transmission of HIV.